Economic valuation of agricultural land conversion to oil palm plantations: Assessing economic benefits and environmental impacts - Sari, Pepy Hapita; Erpinda, Mia (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2025)
Background: The conversion of agricultural land into oil palm plantations has become a pressing issue due to its significant economic and environmental impacts. While oil palm production offers economic benefits, it also contributes to biodiversity loss and the degradation of ecosystem services. This study aims to assess both the economic valuation and the environmental consequences of land conversion in Muaro Jambi Regency, addressing the gap in current research regarding the dual impact of this transformation. Methods: A total economic valuation (TEV) approach was applied, combining direct use value (DUV), indirect use value (IUV), and option value (OV) to quantify the economic impacts. Data collection included secondary data from government reports, industry studies, and previous academic works. Statistical methods were employed to estimate the economic contributions and environmental costs associated with land conversion. Findings: The total economic value of converting agricultural land to oil palm plantations was estimated at IDR 1.097 trillion per year, predominantly driven by the direct use value of palm oil production. The conversion, however, resulted in the loss of vital ecosystem services worth IDR 1.55 billion per year, as well as significant biodiversity and cultural heritage loss, valued at IDR 12.37 billion annually. These findings suggest that while oil palm cultivation provides substantial economic benefits, it also presents serious environmental challenges. Conclusion: The study underscores the importance of balancing economic benefits with environmental sustainability in land conversion decisions. Effective policy interventions, such as Payment for Ecosystem Services (PES), sustainability certifications, and land rehabilitation programs, are essential to mitigate the environmental impacts of oil palm plantations. Novelty/Originality of this article: While previous research has focused on the economic benefits, this study addresses the environmental consequences, such as biodiversity loss and ecosystem service degradation, providing a more comprehensive analysis.